The Farmer’s Perspective of Commodity Futures in India - The Road Ahead - Sultana, Nazia (Indian Journal of Finance, 2008)
The success of the capital market reforms motivated the government and the Forwards Market Commission (the commodities regulator) to kick off similar reforms in the commodities market. Thereby, almost all the commodities are allowed to be traded in the futures market from April 2003. Many economists think that we could have major benefits from liberalisation of the agricultural sector. In this case, the question arises about who will maintain the buffer stock, how will we smoothen the price fluctuations, how will farmers not be vulnerable that tomorrow the price will crash when the crop comes out, how will farmers get signals that in the future there will be a great need for wheat or rice. In all these aspects the futures market has a very big role to play. Commodity futures are fast spreading into rural India at a much faster pace than capital market operations. Seeing the immense potential and response from rural India, some companies have begun to pay increased attention to commodity futures markets. In the developed world, the majority of farmers use futures and options in commodity derivatives and even recognised agents quote spot market prices benchmarked to the commodity derivatives’ contract prices. The article aims at providing an understanding of the commodities market and how the commodities traded on the exchange are helpful to the farmers. The idea is to understand the importance of commodity derivatives and learn about the market from the point of view of the Indian farmers. With most of the restrictions being removed, there is a tremendous potential for growth of this market in the country and this paper will also through some light on some of the initiatives taken up by the Government of India and the road ahead for the farmers in this derivative market. A case study of Mentha Oil is also being taken up.